Cellulose-based high-fog-collecting-efficiency fiber and preparation method thereof
Cellulose-based high-fog collection efficiency fibers were prepared by wet spinning of cellulose and PVP, and by constructing groove structures and spindles, the existing fog collection fibers were solved, and the equipment life and cost of the existing fog collection fibers were reduced in high humidity environments, achieving efficient and low-cost moisture collection effect.
Patent Information
- Application Number
- CN202411992636.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing mist-collection fibers have reduced equipment life and are costly in high humidity environments, making it difficult to balance low cost and high efficiency, and traditional methods are difficult to effectively collect moisture using temperature differences and humidity changes in nature.
Cellulose and PVP are used to mold the mist-collecting fibers by wet spinning. By activating cellulose and controlling PVP content, the groove structure on the fiber surface is constructed, and spindles are formed by dipping the activated cellulose and PVDF mixture to improve the mist-collecting efficiency.
The preparation of cellulose-based high fog collection efficiency fibers is achieved, with a fog collection efficiency of 180.62g/(cm²·h), while reducing the preparation cost and equipment maintenance costs, which is suitable for large-scale production and application.
Smart Images

Figure CN119800536A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of mist collection, and in particular relates to a cellulose-based high mist collection efficiency fiber and a preparation method thereof. Background Art
[0002] As people continue to explore natural resources, inspired by the condensation of fog in nature, methods to convert this abundant but underutilized water resource into practically usable fresh water have attracted widespread attention. In this context, the use of fog-collecting fibers to collect fog is an innovative passive water collection method that is widely used in the field of fog collection.
[0003] The current fog collecting fibers mainly rely on external force assistance (such as electricity, magnetic field, etc.) or other complex infrastructure to achieve the purpose of improving fog collection efficiency. These methods can play a role in improvement to a certain extent, but at the same time, there are also shortcomings. For example, with the help of electric-assisted fog collecting fibers, the equipment life is greatly reduced in a long-term high-density humid air environment, and the performance of the fog collecting materials is prone to unstable performance due to their dependence on electricity; fog collecting materials that require complex infrastructure are less likely to have unstable performance in high-humidity environments, but the additional facility construction and maintenance costs greatly increase their costs. Although the above methods have played an important role in the field of fog collection, traditional fog collectors still find it difficult to strike a balance between low cost and high efficiency. The breakthrough lies in their simple and efficient characteristics. Therefore, it is crucial to find a method that can effectively collect moisture by simply utilizing the temperature difference and humidity changes in nature. In recent years, biomaterials have attracted much attention from technicians due to their wide sources and renewable properties. Among them, cellulose is the oldest and most abundant natural polymer on earth. The abundant hydroxyl groups on the β-D-pyranose ring of its molecular skeleton provide natural and efficient hydrophilic regions. It is a renewable material with strong hygroscopicity and the best natural raw material for preparing environmentally friendly and biocompatible materials. Therefore, cellulose-based materials have shown great potential in the preparation of fog-collecting fibers.
[0004] Biomass fog collecting fibers based on cellulose have the following advantages: cellulose's excellent biocompatibility, degradability and strong hygroscopicity make it easy to be applied to the field of advanced functional fibers. Bionics has been widely used in recent years. The Chinese patent with application number CN201811151930.1 and titled "A method for preparing a spider silk-like fiber structure with directional hydrophobicity" mentioned that the Laplace force caused by the surface energy difference between the fiber and the spindle knot on the fiber surface with the special structure of spider silk can cause water droplets to move and gather, but at the same time, due to the limitations of the nature of the substrate itself, it has no obvious effect on the improvement of the fiber fog collection efficiency, and the complex preparation method increases the difficulty of technical implementation while also increasing the preparation cost, which limits the efficiency of the fog collecting fiber. Therefore, the selection of materials that are helpful to improve the fog collection efficiency, simplifying the preparation process and making it more cost-effective while improving the fiber's fog collection efficiency is still an urgent problem to be solved. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a cellulose-based high mist collection efficiency fiber and a preparation method thereof, so as to solve the problem of selecting materials that are helpful in improving the mist collection efficiency, simplifying the preparation process and making it lower in cost while improving the mist collection efficiency of the fiber. The preparation method is simple and has lower cost. Cellulose and PVP are formed into mist collection fibers in one step through wet spinning, thereby improving the mist collection efficiency of the fiber.
[0006] The present invention is achieved through the following technical solutions: A method for preparing a cellulose-based fiber with high mist collection efficiency comprises the following steps: S1, dissolving activated cellulose and polyvinylpyrrolidone in a solvent, wherein the mass ratio of polyvinylpyrrolidone to activated cellulose is (5-30):100, to obtain a spinning solution; S2, spinning the spinning solution in a first water bath by a one-step wet spinning method, collecting fibers with a stretching ratio of 100%-300%, and obtaining cellulose-based high mist collection efficiency fibers.
[0007] A further improvement of the present invention is: S1 activates cellulose according to the following process: The cellulose is activated in N,N-dimethylacetamide at 60-120° C. for 60-120 minutes at a mass ratio of 1:(10-20), and then dried to complete the activation of the cellulose.
[0008] The solvent described in S1 is a solution of LiCl in N,N-dimethylacetamide, and the mass ratio of LiCl to N,N-dimethylacetamide is 1:11. S1 obtains the spinning solution according to the following process: First, the activated cellulose is placed in a LiCl N, N-dimethylacetamide solution, the mass ratio of the activated cellulose to the LiCl N, N-dimethylacetamide solution is 1:24, and after stirring at 55-65° C. for 5.5-6.5 hours, polyvinyl pyrrolidone is added and stirring is continued for 12-24 hours to obtain a spinning solution. When the spinning solution described in S2 is spun, the flow rate of the spinning solution is 2-20 ml / h. Also includes S3: S3, immersing the cellulose-based high fog collection efficiency fiber into the mixed solution of cellulose and PVDF activated in S1 and then pulling it up, wherein the mass ratio of cellulose and PVDF is 3:7, and then performing phase transformation in a second water bath, and then drying at room temperature, forming spindle knots on the surface of the cellulose-based high fog collection efficiency fiber, and obtaining a cellulose-based high fog collection efficiency fiber with a bionic spider silk structure. In the mixed solution described in S3, the total mass percentage of the cellulose and PVDF is 2%-10%, and the solvent is N,N-dimethylacetamide. The pulling rate of S3 is 100-200 mm / min. The drying time at room temperature in S3 is 45-50h. A cellulose-based high mist collection efficiency fiber obtained by any one of the above-mentioned methods for preparing a cellulose-based high mist collection efficiency fiber.
[0009] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a cellulose-based fiber with high fog collection efficiency. After cellulose is activated, the degree of hydrogen bond entanglement between its molecules is reduced, and the solubility of cellulose in a solvent can be further improved, so that it is convenient to dissolve with PVP to prepare a spinning solution, and the cellulose-based fiber with high fog collection efficiency is obtained by controlling the stretching ratio. If the PVP content is less than 5% of the activated cellulose, the precipitation amount is too small, so that a groove structure with a clear orientation cannot be formed on the fiber surface, and the fiber has no obvious effect on improving the fog collection efficiency. When the PVP addition amount is 10%, the groove structure on the fiber surface is the most uniform, and the fog collection efficiency also reaches a maximum value. After further improvement, the fiber surface structure begins to be disordered, and the fog collection efficiency also decreases. If it exceeds 30%, excessive precipitation of PVP causes the fiber surface structure to be disordered and agglomeration easily occurs within a range, and a relatively stable structure that is beneficial to fog collection cannot be formed, resulting in a decrease in fog collection efficiency. Therefore, by controlling the mass ratio of polyvinylpyrrolidone to the activated cellulose to (5-30):100, a fiber with a groove structure on the surface can be constructed, and the fog collection efficiency is significantly improved. The raw material source of the present invention is biomass-based cellulose natural material, which is abundant, low in price, and has excellent hydrophilicity and degradability. Cellulose as a fiber material has good biocompatibility and degradability, providing a more sustainable choice for the field of fog collection. It can be prepared in one step, and the preparation method is simple, the cost is lower, the operability is strong, the production efficiency is high, and it is suitable for large-scale production and application. Cellulose and PVP are wet-spun in one step to form fog-collecting fibers, which improves the fog collection efficiency of the fibers.
[0010] Furthermore, by dipping the activated cellulose and PVDF mixed liquid on the surface of the cellulose-based high fog collection efficiency fiber, the spindle knot can be continuously formed with the help of phase inversion in the second water bath and room temperature drying. The phase inversion in the second water bath can transform the dipping liquid remaining on the fiber surface from liquid to solid. The driving force generated by a certain curvature gradient of the spindle knot has a favorable effect on the improvement of the fiber fog collection efficiency. At the same time, the hydrophilic and hydrophobic properties of the dipping liquid in a certain ratio will cause a wettability gradient from the fiber surface to the spindle knot, which has a positive effect on the fiber fog collection efficiency. The obtained cellulose-based high fog collection efficiency fiber with a bionic spider silk structure is placed on a bracket in an environment of 25°C. Due to the presence of a uniformly oriented groove structure on the fiber surface, when the fog flows through, the groove structure on the fiber surface increases the effective contact area between the fiber and the fog, and can provide a large amount of capillary force, accelerate the capture of fog, and quickly generate tiny droplets on the fiber surface. At the same time, the introduction of the spindle knot further improves the fiber's water collection capacity and droplet suspension capacity. After the droplets are captured on the fiber surface, they are transported along the groove structure toward the spindle knot, and then grow in situ on the spindle knot. After reaching the critical droplet volume, they fall and are collected under the action of gravity. During the droplet transportation process, due to the existence of the groove structure, a liquid film will be formed between adjacent groove structures, which can provide a continuous internal driving force to complete the entire transportation process quickly, thereby improving the fiber's fog collection and transmission performance, and the fog collection efficiency can reach 180.62g / (cm²·h). It is a simple and efficient solution with great potential in the field of fog collection materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a sample picture of the cellulose-based high-efficiency mist collection fiber (PVP fiber) prepared in Example 3 of the present invention.
[0012] Figure 2a This is a scanning electron microscope image of the cellulose filaments (denoted as C) obtained in Example 1 of the present invention.
[0013] Figure 2b This is a scanning electron microscope image of the cellulose-based high-efficiency mist collection fiber (PVP fiber, denoted as P) obtained in Example 3 of the present invention.
[0014] Figure 3a It is a comparison chart of the mist collection efficiency of the cellulose filaments (denoted as C) obtained in Example 1 of the present invention and the cellulose-based high-efficiency mist collection fibers (denoted as P) obtained in Example 3.
[0015] Figure 3b This is a comparison chart of the mist collection efficiency of bionic spider silk cellulose silk (denoted as CF) and PVP silk (denoted as PCF) after constructing the spindle knot structure in Example 7 of the present invention.
[0016] Figure 4This is a diagram of the mist collection process of the bionic spider silk high-efficiency mist collection fiber (PCF) prepared in Example 7 of the present invention. DETAILED DESCRIPTION
[0017] The technical solution of the present invention will be clearly and completely described below in conjunction with specific drawings, process steps, implementation conditions and materials. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The present invention provides a method for preparing a cellulose-based fiber with high mist collection efficiency, comprising the following steps: 1) After cellulose is activated (activated in an activator and then dried, with the mass ratio of activator to cellulose being 10-20:1), the degree of hydrogen bond entanglement between cellulose molecules is reduced, further improving the solubility of cellulose in solvents.
[0019] The activating agent of the activation process is N, N-dimethylacetamide (DMAc), the activation temperature is 60-120°C, and the activation time is 60-120 min.
[0020] Specifically, the solvent is LiCl in N,N-dimethylacetamide solution, the mass ratio of LiCl to N,N-dimethylacetamide is 1:11, the activated cellulose is first placed in the solvent, the mass ratio of the activated cellulose to the solvent is 1:24, heated in a 60°C water bath and stirred for 6 hours, then PVP is added and stirred for 12-24 hours to obtain a uniform spinning solution.
[0021] 3) The spinning solution is spun in the first water bath (the coagulation bath is water) by a one-step wet spinning method. The flow rate of the spinning solution is 2-20 ml / h. The transformation from liquid phase to solid phase is completed during the spinning process. Fibers with a stretching ratio of 100%-300% are collected to obtain cellulose-based high-efficiency mist collection fibers (a groove structure is successfully constructed on the fiber surface).
[0022] 4) The wet-spun fibers are immersed in a mixture of activated cellulose (hereinafter referred to as cellulose) and PVDF (the solvent is N,N-dimethylacetamide, the mass ratio of cellulose to PVDF is 3:7, and the total mass percentage of cellulose to PVDF is 2wt%-10wt%), and then pulled at a pulling rate of 100-200 mm / min. With the help of the Rayleigh instability principle, the impregnation liquid forms a spindle knot with a certain hydrophobicity on the fiber surface, thereby obtaining a cellulose-based bionic spider silk high-efficiency mist-collecting fiber.
[0023] 5) The fiber obtained by S4 is then immersed in a second water bath (the coagulation bath is water) for a second phase transformation (the coating liquid that forms the spindle knot on the fiber surface is transformed from liquid to solid, reducing the subsequent drying time). After drying at room temperature for 45-50 hours, the final cellulose-based bionic spider silk high-efficiency fog-collecting fiber is obtained (the fiber with a groove structure on the surface successfully introduces the spindle knot structure).
[0024] When the amount of PVP added is 10% of the activated cellulose, the groove structure on the fiber surface is the most uniform and the mist collection efficiency reaches the maximum value. After further improvement, the fiber surface structure begins to become disordered and the mist collection efficiency also decreases. This is mainly due to excessive precipitation of PVP, which is prone to agglomeration and causes obvious damage to the fiber surface structure.
[0025] By dipping 2wt%, 4wt%, 6wt%, 8wt% and 10wt% of cellulose and PVDF mixed liquid on the fiber surface, the spindle knot (bionic spider silk structure) is further formed. The driving force generated by the curvature gradient is beneficial to the fiber transmission process. At the same time, the hydrophilic and hydrophobic properties of the dipping liquid in a certain ratio will cause a wettability gradient from the fiber surface to the spindle knot. The driving force generated by the wettability gradient is also beneficial to improve the water conductivity of the fiber. In addition, the spindle knot surface with a certain hydrophobicity can reduce the pinning phenomenon on the fiber surface caused by the excessive hydrophilicity of cellulose, thereby accelerating the droplet falling. The size and dimensions of the spindle knot can be controlled by controlling the concentration of the dipping solution and the pulling speed. As the concentration of the mixed solution and the pulling speed increase, the size and spacing of the spindle knots also increase by utilizing the Rayleigh instability, and the curvature of the junction between the spindle knot and the fiber also increases. However, when the concentration of the dipping solution exceeds 6wt%, the solution becomes viscous and it is difficult to fall naturally by gravity alone. The shape of the spindle knot is not easy to be completely formed, and the curvature gradient between the spindle knot and the fiber surface begins to decrease. Too much dipping solution will also remain on the fiber surface, which will have a filling effect on the groove structure of the fiber surface itself. When the concentration of the dipping solution exceeds 10wt%, most of the solution is retained on the fiber surface, filling the groove structure on the fiber surface while failing to form a completely shaped spindle knot.
[0026] Example 1 Take 100g of DMAc, add 10g of cellulose, activate at 120℃ for 60min, and dry to obtain the activated cellulose.
[0027] 0.8 g of LiCl was dissolved in 8.8 g of DMAc, and then 0.4 g of activated cellulose was dissolved, and the mixture was stirred at 60° C. for 6 h to obtain a uniform spinning solution.
[0028] The spinning solution was injected into a syringe with a needle diameter of 0.60 mm and connected to a wet spinning device. The extrusion speed, coagulation bath distance and winding speed were all maintained at 4 mL / h, 0.6 m and 12 cm / s, the coagulation bath was water, the temperature was 35°C, the time was 15 seconds, and the stretching ratio was 200%, and cellulose filaments (denoted as C) were obtained. The spinning process was carried out at an ambient temperature of 25°C.
[0029] Example 2 Take 100g of DMAc, add 10g of cellulose, activate at 120℃ for 60min, and dry to obtain the activated cellulose.
[0030] 0.8 g of LiCl was dissolved in 8.8 g of DMAc, and then 0.4 g of activated cellulose was dissolved, and the mixture was stirred at 60° C. for 6 h. Then 0.02 g of PVP was added and stirred for 12 h to obtain a uniform spinning solution.
[0031] The spinning solution was injected into a syringe with a needle diameter of 0.60 mm and connected to a wet spinning device. The extrusion speed, coagulation bath distance and winding speed were all maintained at 4 mL / h, 0.6 m and 12 cm / s, the coagulation bath was water, the temperature was 35°C, the time was 15 seconds, and the stretching ratio was 200%, and cellulose-based high-efficiency mist collection fibers were obtained. The spinning process was carried out at an ambient temperature of 25°C.
[0032] Example 3 Take 100g of DMAc, add 10g of cellulose, activate at 120℃ for 60min, and dry to obtain the activated cellulose.
[0033] 0.8 g of LiCl was dissolved in 8.8 g of DMAc, and then 0.4 g of activated cellulose was dissolved, and the mixture was stirred at 60° C. for 6 h. Then 0.04 g of PVP was added and stirred for 12 h to obtain a uniform spinning solution.
[0034] The spinning solution was injected into a syringe with a needle diameter of 0.60 mm and connected to a wet spinning device. The extrusion speed, coagulation bath distance and winding speed were all maintained at 4 mL / h, 0.6 m and 12 cm / s, the coagulation bath was water, the temperature was 35°C, the time was 15 seconds, and the stretching ratio was 200%, and cellulose-based high-efficiency mist collection fiber (PVP fiber, denoted as P) was obtained. The spinning process was carried out at an ambient temperature of 25°C.
[0035] Example 4 Take 100g of DMAC, add 10g of cellulose, activate at 120℃ for 60min, and dry to obtain the activated cellulose.
[0036] 0.8 g LiCl was dissolved in 8.8 g DMAc, and then 0.4 g activated cellulose was dissolved, stirred at 60° C. for 6 h, and then 0.06 g PVP was added and stirred for 12 h to obtain a uniform spinning solution.
[0037] The spinning solution was injected into a syringe with a needle diameter of 0.60 mm and connected to a wet spinning device. The extrusion speed, coagulation bath distance and winding speed were all maintained at 4 mL / h, 0.6 m and 12 cm / s, the coagulation bath was water, the temperature was 35°C, the time was 15 seconds, and the stretching ratio was 200%, and cellulose-based high-efficiency mist collection fibers were obtained. The spinning process was carried out at an ambient temperature of 25°C.
[0038] Example 5 Take 100g of DMAC, add 10g of cellulose, activate at 120℃ for 60min, and dry to obtain the activated cellulose.
[0039] 0.8 g of LiCl was dissolved in 8.8 g of DMAc, and then 0.4 g of activated cellulose was dissolved, and the mixture was stirred at 60° C. for 6 h. Then 0.04 g of PVP was added and stirred for 12 h to obtain a uniform spinning solution.
[0040] The spinning solution was injected into a syringe with a needle diameter of 0.60 mm and connected to a wet spinning device. The extrusion speed, coagulation bath distance and winding speed were all maintained at 4 mL / h, 0.6 m and 12 cm / s, the coagulation bath was water, the temperature was 35°C, the time was 15 seconds, and the stretching ratio was 200%. The spinning process was carried out at an ambient temperature of 25°C.
[0041] The fibers obtained above are then immersed in a 2wt% mixture of cellulose and PVDF at a pulling rate of 150mm / min to form a spindle knot with hydrophilic and hydrophobic properties on the fiber surface. The fibers then enter a second water bath for a second heavy phase transformation (temperature 40°C, time 20 seconds). After drying at room temperature for 48 hours, cellulose-based bionic spider silk high-efficiency fog-collecting fibers can be obtained.
[0042] Example 6 Take 100g of DMAC, add 10g of cellulose, activate at 120℃ for 60min, and dry to obtain the activated cellulose.
[0043] 0.8 g of LiCl was dissolved in 8.8 g of DMAc, and then 0.4 g of activated cellulose was dissolved, and the mixture was stirred at 60° C. for 6 h. Then 0.04 g of PVP was added and stirred for 12 h to obtain a uniform spinning solution.
[0044] The spinning solution was injected into a syringe with a needle diameter of 0.60 mm and connected to a wet spinning device. The extrusion speed, coagulation bath distance and winding speed were all maintained at 4 mL / h, 0.6 m and 12 cm / s, the coagulation bath was water, the temperature was 35°C, the time was 15 seconds, and the stretching ratio was 200%. The spinning process was carried out at an ambient temperature of 25°C.
[0045] The fibers obtained above are then immersed in a 4wt% mixture of cellulose and PVDF at a pulling rate of 150mm / min to form a spindle knot with hydrophilic and hydrophobic properties on the fiber surface. The fibers then enter a second water bath for a second heavy phase transformation (temperature 40°C, time 20 seconds). After drying at room temperature for 48 hours, cellulose-based bionic spider silk high-efficiency fog-collecting fibers can be obtained.
[0046] Example 7 Take 100g of DMAC, add 10g of cellulose, activate at 120℃ for 60min, and dry to obtain the activated cellulose.
[0047] 0.8 g of LiCl was dissolved in 8.8 g of DMAc, and then 0.4 g of activated cellulose was dissolved, and the mixture was stirred at 60° C. for 6 h. Then 0.04 g of PVP was added and stirred for 12 h to obtain a uniform spinning solution.
[0048] The spinning solution was injected into a syringe with a needle diameter of 0.60 mm and connected to a wet spinning device. The extrusion speed, coagulation bath distance and winding speed were all maintained at 4 mL / h, 0.6 m and 12 cm / s, the coagulation bath was water, the temperature was 35°C, the time was 15 seconds, and the stretching ratio was 200%. The spinning process was carried out at an ambient temperature of 25°C.
[0049] The fiber obtained above is then immersed in a 6wt% mixed solution of cellulose and PVDF at a pulling rate of 150mm / min to form a spindle knot with hydrophilic and hydrophobic properties on the fiber surface, and then enters a second water bath for a second heavy phase transformation (temperature of 40°C, time of 20 seconds). After drying at room temperature for 48 hours, a cellulose-based bionic spider silk high-efficiency fog-collecting fiber (denoted as PCF) can be obtained. The cellulose fiber C of Example 1 is operated according to this step, and the obtained fiber is denoted as CF.
[0050] Example 8 Take 100g of DMAC, add 10g of cellulose, activate at 120℃ for 60min, and dry to obtain the activated cellulose.
[0051] 0.8 g of LiCl was dissolved in 8.8 g of DMAc, and then 0.4 g of activated cellulose was dissolved, and the mixture was stirred at 60° C. for 6 h. Then 0.04 g of PVP was added and stirred for 12 h to obtain a uniform spinning solution.
[0052] The spinning solution was injected into a syringe with a needle diameter of 0.60 mm and connected to a wet spinning device. The extrusion speed, coagulation bath distance and winding speed were all maintained at 4 mL / h, 0.6 m and 12 cm / s, the coagulation bath was water, the temperature was 35°C, the time was 15 seconds, and the stretching ratio was 200%. The spinning process was carried out at an ambient temperature of 25°C.
[0053] The fibers obtained above are then immersed in an 8wt% mixture of cellulose and PVDF at a pulling rate of 150mm / min to form a spindle knot with hydrophilic and hydrophobic properties on the fiber surface. The fibers then enter a second water bath for a second heavy phase transformation (temperature 40°C, time 20 seconds). After drying at room temperature for 48 hours, cellulose-based bionic spider silk high-efficiency fog-collecting fibers can be obtained.
[0054] like Figure 1 As shown, the prepared high-efficiency mist-collecting fiber is collected on a take-up roller, and the surface of the prepared fiber is uniform.
[0055] like Figure 2a and Figure 2b The surface SEM comparison images of the cellulose filaments (C) prepared in Example 1 and the mist-collecting fibers (P) prepared in Example 3 respectively show that a uniform groove structure is successfully constructed on the fiber surface after the addition of PVP. Figure 3a The mist collection efficiencies of the cellulose filaments (C) prepared in Example 1 and the cellulose-based high-efficiency mist collection fibers (P) prepared in Example 3 are demonstrated. It is obvious from the figure that the mist collection efficiency of the fibers (P) with a groove structure on the surface is significantly improved, which further verifies the effect of the groove structure on improving the mist collection performance of the fibers.
[0056] Figure 3b The figure shows the mist collection efficiency of bionic spider silk cellulose silk (CF) and PVP silk (PCF) after adding the spindle knot structure in Example 7. It is easy to see from the figure that the introduction of the spindle knot can further improve the mist collection performance of the fiber. The PCF surface has both groove structure and spindle knot structure, and the mist collection efficiency of the fiber is optimal at this time.
[0057] The fiber of Example 7 was placed on a U-shaped bracket, and a commercial humidifier (YC-D205, Beijing Yadu Technology Co., Ltd.) was used to generate a simulated mist flow, and the mist was directed at the fiber. The volume of the generated mist flow was 300 mL / h, and the distance between the humidifier and the fiber was kept constant (5 cm). A glass plate was placed directly below the fiber as a collection device to collect the droplets captured by the fiber. During the entire experiment, the environmental conditions were controlled, the temperature was maintained at 25±3°C, and the relative humidity was maintained at 50±10%RH. The changes in the mist collection on the fiber were recorded over time. Figure 4A complete water cycle on the fiber (i.e. the process from when the fiber contacts the mist and starts collecting on the surface until the first complete droplet falls and is collected) takes only 36 seconds, and the mist collection efficiency can reach 180.62g / (cm²·h).
Claims
1. A method for preparing a cellulose-based fiber with high mist collection efficiency, characterized in that: The following steps are involved: S1, dissolving activated cellulose and polyvinylpyrrolidone in a solvent, wherein the mass ratio of polyvinylpyrrolidone to activated cellulose is (5-30):100, to obtain a spinning solution; S2, spinning the spinning solution in a first water bath by a one-step wet spinning method, collecting fibers with a stretching ratio of 100%-300%, and obtaining cellulose-based high mist collection efficiency fibers.
2. The method for preparing the cellulose-based high mist collection efficiency fiber according to claim 1, characterized in that: S1 activates cellulose according to the following process: The cellulose is activated in N,N-dimethylacetamide at 60-120° C. for 60-120 min at a mass ratio of 1:(10-20), and then dried to complete the activation of the cellulose.
3. The method for preparing the cellulose-based high mist collection efficiency fiber according to claim 1, characterized in that: The solvent described in S1 is a solution of LiCl in N,N-dimethylacetamide, and the mass ratio of LiCl to N,N-dimethylacetamide is 1:
11.
4. The method for preparing the cellulose-based high mist collection efficiency fiber according to claim 3, characterized in that: S1 obtains the spinning solution according to the following process: First, the activated cellulose is placed in a LiCl N, N-dimethylacetamide solution, the mass ratio of the activated cellulose to the LiCl N, N-dimethylacetamide solution is 1:24, and after stirring at 55-65° C. for 5.5-6.5 hours, polyvinyl pyrrolidone is added and stirring is continued for 12-24 hours to obtain a spinning solution.
5. The method for preparing the cellulose-based high mist collection efficiency fiber according to claim 1, characterized in that: When the spinning solution described in S2 is spun, the flow rate of the spinning solution is 2-20 ml / h.
6. The method for preparing the cellulose-based high mist collection efficiency fiber according to claim 1, characterized in that: Also includes S3: S3, immersing the cellulose-based high fog collection efficiency fiber into the mixed solution of cellulose and PVDF activated in S1 and then pulling it up, wherein the mass ratio of cellulose and PVDF is 3:7, and then performing phase transformation in a second water bath, and then drying at room temperature, forming spindle knots on the surface of the cellulose-based high fog collection efficiency fiber, and obtaining a cellulose-based high fog collection efficiency fiber with a bionic spider silk structure.
7. The method for preparing the cellulose-based high mist collection efficiency fiber according to claim 6, characterized in that: In the mixed solution described in S3, the total mass percentage of the cellulose and PVDF is 2%-10%, and the solvent is N,N-dimethylacetamide.
8. The method for preparing the cellulose-based high mist collection efficiency fiber according to claim 1, characterized in that: The pulling rate of S3 is 100-200 mm / min.
9. The method for preparing the cellulose-based high mist collection efficiency fiber according to claim 1, characterized in that: The drying time at room temperature in S3 is 45-50h.
10. A cellulose-based fiber with high mist collection efficiency obtained by the preparation method of the cellulose-based fiber with high mist collection efficiency according to any one of claims 1 to 9.
Citation Information
Patent Citations
A method for preparing spider silk-like fiber structures with directional hydrophobicity
CN109137102B
Method of using non-adhesive method to prepare cellulose base fiber
CN101550614A
Preparation method of freshwater collecting fibers with transmission function and application thereof
CN102587139A
Super-hydrophobic nanofiber, fibrous membrane and preparation method and application thereof
CN110777533A
Nanofiber membrane material for cleansing cotton and preparation method of nanofiber membrane material
CN113907501A